Tip‐enhanced Raman spectroscopy – an interlaboratory reproducibility and comparison study. (9th January 2014) - Blum, Carolin; Opilik, Lothar; Atkin, Joanna M.; Braun, Kai; Kämmer, Stefan B.; Kravtsov, Vasily; Kumar, Naresh; Lemeshko, Sergey; Li, Jian‐Feng; Luszcz, Karol; Maleki, Teimour; Meixner, Alfred J.; et al.
<x xml:space="preserve">Abstract</x> Since its first experimental realization, tip‐enhanced Raman spectroscopy (TERS) has emerged as a potentially powerful nanochemical analysis tool. However, questions about the comparability and reproducibility of TERS data have emerged. This interlaboratory comparison study addresses these issues by bringing together different TERS groups to perform TERS measurements on nominally identical samples. Based on the spectra obtained, the absolute and relative peak positions, number of bands, peak intensity ratios, and comparability to reference Raman and surface‐enhanced Raman spectroscopy (SERS) data are discussed. Our general findings are that all research groups obtained similar spectral patterns, irrespective of the setup or tip that was used. The TERS (and SERS) spectra consistently showed fewer bands than the conventional Raman spectrum. When comparing these three methods, the spectral pattern match and substance identification is readily possible. Absolute and relative peak positions of the three major signals of thiophenol scattered by 19 and 9 cm−1, respectively, which can probably be attributed to different spectrometer calibrations. However, within the same group (but between different tips), the signals only scattered by 3 cm−1 on average. This study demonstrated the suitability of TERS as an analytical tool and brings TERS a big step forward to becoming a routine technique. Copyright © 2014 John Wiley & Sons, Ltd.